Structural Insights into Dissimilatory Sulfite Reductases: Structure of Desulforubidin from Desulfomicrobium Norvegicum - Oliveira, Tania F.; Franklin, Edward; Afonso, José P.; Khan, Amir R.; Oldham, Neil J.; Pereira, Inês A. C.; Archer, Margarida (Frontiers in Microbiology, 2011)
Dissimilatory sulfite reductases (dSiRs) are crucial enzymes in bacterial sulfur-based energy metabolism, which is likely to have been present in some of the earliest life forms on Earth. Several classes of dSiRs have been proposed on the basis of different biochemical and spectroscopic properties. Here, we describe the first structure of a dSiR from the desulforubidin (Drub) class isolated from Desulfomicrobium (Dm.) norvegicum. The desulforubidin structure is assembled as a2b2c2, in which two DsrC proteins are bound to the core [DsrA]2[DsrB]2 unit, as reported for the desulfoviridin (Dvir) structure from Desulfovibrio (D.) vulgaris. Unlike desulfoviridin, four sirohemes and eight [4Fe-4S] clusters are present in desulforubidin, but only two of the coupled siroheme-[4Fe-4S] cofactors are likely to be catalytically active. Mass spectrometry studies of purified desulforubidin and desulfoviridin show that both proteins may present different oligomeric complex forms that bind two, one or no DsrC proteins, providing an explanation for conflicting spectroscopic and biochemical results in the literature.